Participatory Training Activities in South Asia for Promoting Safety and Health in Informal Economy Workplaces—Roles of Trade Unions and Employer Organizations - Tsuyoshi Kawakami (Safety and Health at Work)
Workers and employers in the informal economy are often outside the scope of legal frameworks of occupational safety and health (OSH) service in South Asia. The present study aimed to find practical support measures to improve their safety and health. International Labour Organization’s participatory training activities in five selected informal economy workplaces comprising waste collection and recycling in India, sewage cleaning in Pakistan, home-based manufacturing in Nepal, small-scale construction in Nepal, and cotton farming in India were studied. The common steps taken in the training were collaboration with local trade unions and employer organizations to reach informal economy workplaces, collection of local good practices in OSH for designing participatory training contents, training worker and employer OSH trainers, assisting trained worker and employer trainers in conducting cascading training activities in their own workplaces, and follow-up visits for support and sustainability. It was found that working with local trade unions and employer organizations had the strong potential to reach various informal economy workplaces. Applying the easy-to-apply participatory training methodologies was vital in delivering practical OSH support.